Drivers of functional diversity in the hyporheic zone of a large river - Gaur, Shishir; Graillot, Didier; Paran, Frederic; Marmonier, Pierre; Dole-Olivier, Marie-José; Creuzé des Châtelliers, Michel; Galassi, Diana M.P.; Lafont, Michel; Mermillod-Blondin, Florian (Elsevier B.V., 2022)
The effects of regional (hydrogeology and geomorphology) and local (sediment and hydrology) characteristics on hyporheic assemblages were studied along a 40-km reach of a large gravel-bed river. Hyporheic water and fauna were sampled at the upstream and downstream positions of 15 large gravel bars. The resulting 30 stations varied in their sediment grain size, stability and direction of river-aquifer exchanges. The study concludes that at the 40-km (sector) scale, the longitudinal distribution of hyporheic fauna was controlled by 1) the hydrogeology of the valley (i.e. gaining vs loosing sectors) that modifies abundance and taxonomic richness of stygobites 2) current channel morphometry of the river (i.e. shape and location of meanders), and 3) historical changes (i.e. river incision) which modify abundance and richness of assemblages. At the local scale, we found that surface grain size and stability of the sediment evaluated by visual observation were poor predictors of hyporheos composition. In contrast, the local hydrology (i.e. downwellings, upwellings, low vertical exchanges) explained a large part of the abundance, taxonomic richness and composition of the hyporheic assemblages. Stations with low vertical exchanges were found poorly colonized, while the upwelling zones were rich in stygobites and downwelling areas harbor abundant and species-rich temporary hyporheos. It was also observed that functional diversity was controlled by the same parameters, with high relative abundances of stygobites in upwelling zones and POM feeders in downwelling zones. The heterogeneity of hydrological patterns, with alternation of upwellings and downwellings may represent the optimal spatial structure for hyporheic biodiversity conservation and resilience in rivers.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Dams; Geomorphology; Hydrogeology; Hyporheos; River incision; Stygobites